Ingresos y gastos operativos de la Empresa Babahoyo Al Dia “Baldía S.A.S.” en el periodo 2022 - 2023. - Onofre Cepeda, Carmen Andrea (2025)
The company Babahoyo al Día “Baldía S.A.S.” experienced financial difficulties between 2022 and 2023 due to poor management of revenues and operating expenses. The lack of an effective commercial strategy and increased competition caused a 24.38% reduction in revenue. In addition, the economic crisis affected consumers' purchasing capacity, further reducing sales. On the other hand, operating expenses increased by 6.43%, mainly due to inefficient management of internal resources, increased costs of raw materials, infrastructure maintenance and administrative expenses. This created a financial gap that compromised the sustainability of the company. Financial analysis reveals that the gross profit margin decreased from 10.23% in 2022 to 8.87% in 2023, while the operating margin fell from 4.63% to 1.31%. To reverse this trend, it is recommended to implement strict expense control, optimize financial planning and diversify income sources. In addition, it is essential to strengthen commercial strategies and carry out internal audits to correct inefficiencies. If adequate measures are not taken, the company will face a more severe economic crisis that will affect its stability and positioning in the market.